Comparative transcriptional profiling of regenerating damaged knee joints in two animal models of the newt Notophthalmus viridescens strengthens the role of candidate genes involved in osteoarthritis. Issue 3 (September 2022) - Geyer, Matthias; Schönfeld, Christiane; Schreiyäck, Carina; Susanto, Sony A.; Michel, Christian; Looso, Mario; Braun, Thomas; Borchardt, Thilo; Neumann, Elena; Müller-Ladner, Ulf
Abstract: Objectives: To compare joint regeneration in adult newts ( N. viridescens ) upon both newly established surgical removal and previously reported enzymatic destruction of articular cartilage to identify molecular factors and functionally analyze potentially important regulators involved in osteoarthritis (OA). Methods: Damage of knee cartilage was induced by either intra-articular injection of collagenase or by surgical removal of articular cartilage as a novel additional approach. Changes over time were clinically and histologically analyzed and studied by cDNA microarray analysis, real-time quantitative PCR, immunohistochemistry and functional assays to identify relevant candidate genes and determine their impact on regeneration. Results: Several genes were found to be up-regulated during regeneration, including extracellular matrix components and mediators of cell-matrix interactions, genes encoding for cellular components, for cell and tissue homeostasis and tissue remodelling, for cellular processes as well as signalling molecules. A high activity and diversity of transcription was detected on days 10 and 20, especially in the surgical model. 10 candidate genes were further analyzed. The matricellular protein tenascin C (TN-C) attracted our particular attention due to its prominent up-regulation during regeneration in both models and at different time points. Conclusions: Newts are able to regenerate OA-like articular cartilage damage ad integrum both after enzymatic and mechanical injury. Most of the genes involved in amphibians are also known to be operative in humans and other mammals, especially matricellular factors interfering with optimized matrix remodelling. Our results stress the necessity to elucidate mechanistic differences in different species potentially using identical molecules but with different functional results.